Analisis Pengaruh Faktor Stres terhadap Motivasi Pekerja - Johan Wirawan; Leli Deswindi (Universitas Bunda Mulia, 2017)
The problem of stress is sometimes unconsciously influence the way a worker thinks. Job stress can have a positive or negative impact for a worker. If excessive stress it will have negative and if the stress is still within normal limits, then the stress can trigger the motivation of workers. In this research, it will be discussed will be the relationship between stress and worker motivation whether significant or not, and will also be discussed about the influence of both stress factors related to the organization or not. Stress factors associated with organizations that are determined in this research are the workload and work environment. Stress factors that are not related to the organization is the type of personality and family. The workload is too heavy will make workers become frustrated and lose motivation of workers. Vice versa if the workload is too light then the worker will experience a saturation that is also not motivated to work. This research will also be discussed further factor which affects the motivation of workers. Research suggests that stress variables have a significant relationship with motivation variables. This is done with regression testing and also correlation with several methods. Figures generated R square is for 0.504 which means the 50.4% contribution in terms of stress variables affecting motivation variable while 49.6% influenced other factors. The research results are obtained also found that internal stress factors or office stress factors related to the organization over affect the motivation of workers rather than stress factors unrelated to the organization. It also found that more office internal stress factors play a role in influencing workers' job stress. In addition, correlation of test results found places correlation between workload and working environment with the motivation was for 0.708 and for the type of personality and family is at 0.485 so that internal stress factors play a role in affecting the office worker motivation.